Nonuraemic calciphylaxis: response to treatment with pamidronate and negative pressure therapy. (1st January 2015) - Lorriaux, A.; Chaby, G.; Dhaille, F.; Dadban, A.; Arnault, J. P.; Dhillies, A. S.; Lombart, F.; Chatelain, D.; Lok, C.
Summary: Calciphylaxis is a rare cause of skin ulcerations and necrosis in patients with both normal renal and parathyroid function. Although calciphylaxis appears to be on the increase, treatments are mainly empirical, especially for wound care. The lesions in calciphylaxis are typically very painful and carry a high risk of infection, with sepsis being the leading cause of death in this serious disease. We report two cases of nonuraemic calciphylaxis, which responded to treatment with pamidronate and wound management by negative pressure system.